Commutators in special linear groups over certain division rings - Bien, M. H.; Lam, P. L. P.; Mai, V. T. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 512.5We consider the question whether an element of a special linear group  ${\rm SL}_m(D)$ of degree $m\ge 1$ over a division ring $D$  is a commutator. Our first aim  is to show that if the division ring $D$ is algebraically closed and finite-dimensional over its center, then every element of ${\rm SL}_m(D)$ is a commutator of ${\rm SL}_m(D).$  We also indicate that this question  is related to the derived series in division rings and then describe the derived series in the Mal'cev–Neumann division rings of noncyclic free groups over fields.